Anxiety and related factors in frontline clinical nurses fighting COVID-19 in Wuhan. Issue 30 (24th July 2020) - Li, Ruilin; Chen, Youlin; Lv, Jianlin; Liu, Linlin; Zong, Shiqin; Li, Hanxia; Li, Hong
Abstract : Abstract: The aim of this study was to examine the anxiety status of the frontline clinical nurses in the designated hospitals for the treatment of coronavirus disease 2019 (COVID-19) in Wuhan and to analyze the influencing factors, to provide data for psychologic nursing. This study used a cross-sectional survey design and convenience sampling. The questionnaires were completed by 176 frontline clinical nurses. Anxiety was determined using the Hamilton anxiety scale. General data were collected using a survey. Correlation analyses were used. Among the 176 frontline nurses, 77.3% (136/176) had anxiety. The anxiety scores of the frontline clinical nurse fighting COVID-19 were 17.1 ± 8.1. Anxiety symptoms, mild to moderate anxiety symptoms, and severe anxiety symptoms were found in 27.3%, 25%, and 25% of the nurses, respectively. Sex, age, marital status, length of service, and clinical working time against COVID-19 were associated with anxiety ( P  < .05). The frontline nurses working in the designated hospitals for the treatment of COVID-19 in Wuhan had serious anxiety. Sex, age, length of service, and clinical working time against COVID-19 were associated with anxiety in those nurses. Psychologic care guidance, counseling, and social support should be provided to the nurses to reduce their physical and mental burden. Nursing human resources in each province should be adjusted according to each province's reality.